2014
DOI: 10.1007/s00204-014-1262-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular fibril formation, calcification, and enrichment of chaperones, cytoskeletal, and intermediate filament proteins in the adult hippocampus CA1 following neonatal exposure to the nonprotein amino acid BMAA

Abstract: The environmental neurotoxin β-N-methylamino-l-alanine (BMAA) has been implicated in the etiology of neurodegenerative disease, and recent studies indicate that BMAA can be misincorporated into proteins. BMAA is a developmental neurotoxicant that can induce long-term learning and memory deficits, as well as regionally restricted neuronal degeneration and mineralization in the hippocampal CA1. The aim of the study was to characterize long-term changes (2 weeks to 6 months) further in the brain of adult rats tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 72 publications
3
45
0
Order By: Relevance
“…Ultrastructural examination by transmission electron microscopy revealed intracellular deposition of abundant bundles of closely packed parallel fibrils in neurons, axons and astrocytes of the CA1. SIMS IMS and laser capture microdissection followed by LC–MS/MS showed enrichment of specific phospholipids and proteins in this brain region (Hanrieder et al 2014a, b; Karlsson et al 2015a, b). These molecular studies of BMAA-induced effects further illustrate the usefulness of combining IMS with other experimental techniques to identify target regions and investigate toxicological events.
Fig.
…”
Section: Imaging Mass Spectrometry In Mechanistic Toxicologymentioning
confidence: 99%
“…Ultrastructural examination by transmission electron microscopy revealed intracellular deposition of abundant bundles of closely packed parallel fibrils in neurons, axons and astrocytes of the CA1. SIMS IMS and laser capture microdissection followed by LC–MS/MS showed enrichment of specific phospholipids and proteins in this brain region (Hanrieder et al 2014a, b; Karlsson et al 2015a, b). These molecular studies of BMAA-induced effects further illustrate the usefulness of combining IMS with other experimental techniques to identify target regions and investigate toxicological events.
Fig.
…”
Section: Imaging Mass Spectrometry In Mechanistic Toxicologymentioning
confidence: 99%
“…BMAA is considered to have a low neurotoxic potency in adult rodents (Perry et al 1989; Cruz-Aguado et al 2006). However, BMAA is a developmental neurotoxin inducing long-term cognitive deficits as well as neurodegeneration, astrogliosis, and intracellular fibril formation in the hippocampus of adult rodents following neonatal exposure to BMAA (Karlsson et al 2009b, 2014). BMAA also induces behavioral changes in neonates and perturbs serum metabolites that are associated with changes in energy metabolism and amino acid metabolism (Karlsson et al 2009a; Engskog et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that BMAA is a mixed glutamate receptor agonist that can induce excitotoxicity in primary neurons in vitro and in vivo (Weiss et al 1989; Zeevalk and Nicklas 1989; Chiu et al 2012) but BMAA is also suggested to induce neurotoxicity through other mechanisms such as oxidative stress (Lobner et al 2014). Recent studies have demonstrated enrichment of proteins implicated in protein aggregation, and an increased protein ubiquitination in the adult hippocampus following neonatal administration suggesting BMAA-induced perturbations of cellular protein homeostasis (Karlsson et al 2014). In addition, a dose-dependent increase of protein-associated BMAA in neonatal rat brain, especially in the hippocampus, has been observed (Karlsson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to a higher dose (460 mg/kg) also induced altered expression of S100β, histones, calcium and calmodulin-binding proteins as well as guanine nucleotide-binding proteins. At this dose; neuronal degeneration, astrogliosis, intracellular fibril formation, and increased protein ubiquitination were evident in the hippocampus of some of the animals [17,19]. Laser microdissection of tissue samples from the affected hippocampal regions was performed and followed by LC–MS/MS based proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%